Pengaruh Jumlah Penduduk dan PDRB terhadap Kemiskinan di Sumatera Utara - Margaretha, Dewi; Purba, Kristin Yenita; Karo-Karo, Laura Elfina; Zebua, Nobel Indah; Feby, Zenifer; Hidayat, Nasrullah (Ikatan Da'i Indonesia, 2024)
Poverty is one of the biggest problems in various developing countries, including Indonesia. All provinces in Indonesia experience poverty, one of which is in North Sumatra Province. Level poverty in North Sumatra Province continues to experience fluctuations and poverty this issue every year is in a serious spotlight. Poverty problems this has to be overcome immediately. Therefore, this study aims to analyzing how much a Large Population and Gross Regional Domestic Product affects poverty in northern Sumatra in 2004 to 2021 both simultaneously and partially. The type of data used in this study is secondary time series data from 2004 to 2021.The data used is data obtained from the official website of the North Sumatra Central Statistics Agency (BPS). The analytical method used in this study is the analysis of multiple linear regression with statistical software and ekonometrika Eviews 12. The results showed that Partially a variable of population and regional gross domestic product had a significant effect on the number of poor people in North Sumatra in 2004 to 2021. The implications that can be given from this research are that population variables are positive and insignificant while gross domestic product is positive and significant to poverty in the province of North Sumatra. then the government of the north sumatra needs to increase human resources through health, education, or increase several supporting aspects so that it does not overflow in accordance with existing job vacancies. so that the number of quality and economically capable population is no longer the driving force of poverty. The northern Sumatra government also needs to equal the regionql grossto domestic product and perform improvements in each sector by exposing potensi- potential.